Investigation of functional and technological properties of crushed milts - Natalia V. Dementeva; Valery D. Bogdanov (Известия ТИНРО)
Fresh milts of salmon, cod, and herring possess high technological properties which are lowered in the processes of freezing and storage. The lowering is insignificant in the first month of storage but becomes more essential after two months of storage, in particular for the milt of cod. One of these properties is a high emulsifying ability. Stability of the emulsion systems with use of milt depends on the fish species, freshness of the raw materials, and preliminary thermal processing: the emulsions with milt of salmon have higher stability relative to the milts of other species and the unprocessed milt provides the highest stability of the emulsion systems. The milts could be used in emulsified products both as the emulsifiers and as functional ingredients that include proteins, nucleic acids, phospholipids, and polyunsaturated fatty acids.